The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1111/j.1365-2125.1991.tb03892.x
|View full text |Cite
|
Sign up to set email alerts
|

The disposition of bupivacaine following a 72 h interpleural infusion in cholecystectomy patients.

Abstract: The disposition of bupivacaine and degree of analgesia following a 72 h interpleural infusion was investigated in 12 adult patients undergoing elective cholecystectomy. The infusion regimen of an initial interpleural bolus dose of 20 ml of 0.5% bupivacaine HCI with adrenaline (1:200,000) followed by continuous infusion at a rate of 8 ml h-1 of 0.25% plain bupivacaine HCI was designed to achieve continuous post-operative pain relief for 72 h. In practice an additional bolus dose (identical to the first) adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Numerous studies demonstrate an acceptable safety profile with bupivacaine administered via the interpleural route [6, 8, 12–14, 16, 19]. In our study we used a conservative dosing regime and found no reported symptoms consistent with local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Numerous studies demonstrate an acceptable safety profile with bupivacaine administered via the interpleural route [6, 8, 12–14, 16, 19]. In our study we used a conservative dosing regime and found no reported symptoms consistent with local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 66%
“…Whilst there are sufficient patients to detect a clinically important difference in the primary endpoint, we are unable to detect the true incidence of complications from interpleural analgesia due to the relatively small sample size. Plasma levo‐bupivacaine levels were not evaluated as they have been well reported in numerous other studies [1, 6, 8, 12, 13, 16, 19, 26]. Although we found no reported symptoms of local anaesthetic toxicity, it is possible that plasma levels may have demonstrated concentrations above the accepted safe range.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…[1][2][3] Toxicity is inconsistent as signs of toxicity have been reported in humans administered doses below the toxic dose, 11 but toxicity did not occur in others administered doses causing plasma concentrations to go higher than that considered toxic. 12,13 Absorption of local anesthetics after extravascular infiltration is dependent on the chemical nature of the drug, where the drug is administered, dose, concentration of the drug, vascularity of the infiltrated site, and the presence or absence of vasoactive drugs such as epinephrine in the anesthetic solution. 4 Extravascular administration of bupivacaine will undergo slow systemic absorption with rapid clearance; hence, plasma concentrations are not expected to reach toxic concentrations.…”
Section: Introductionmentioning
confidence: 99%